Engineering Sciences and Applications - MARROQUÍN-DE JESÚS, Ángel; CASTILLO-MARTÍNEZ, Luz Carmen; OLIVARES-RAMÍREZ, Juan Manuel; MORADO-HUERTA, Guadalupe (ECORFAN-Mexico, 2023)
This paper describes a dynamic activity to teach the concepts of renewable energy and evaluates its effects on engineering students in Mexico. The dynamic activity is based on variations of percentages of energy consumption proposed by a teacher and the participants using bean seeds. A total of 92 students of Renewable Energy Engineering from three different periods involved the study. The participants were divided into groups, and presented a report where they demonstrated their level of understanding. Using the One-Way ANNOVA test determined differences between their proposals and the teacher ones and interpreted the level of participants'knowledge acquired. A survey was also implemented to examine the effects of understanding the topic and detect discrepancies between directed questions and their proposals. The results showed that the dynamic activity helps participants with their difficulties in understanding the topic. It was found satisfactory outcomes when the dynamic activity is applied face to face.